Accurate prediction of neuroblastoma outcome based on miRNA expression profiles - Schulte, Johannes Hubertus; Schowe, Benjamin; Mestdagh, Pieter; Kaderali, Lars; Kalaghatgi, Prabhav; Schlierf, Stefanie; Vermeulen, Joelle; Brockmeyer, Bent; Pajtler, Kristian; Thor, Theresa; de Preter, Katleen; Speleman, Frank; et al. (International journal of cancer, 2010)
For neuroblastoma, the most common extracranial tumour of childhood, identification of new biomarkers and potential therapeutic targets is mandatory to improve risk stratification and survival rates. MicroRNAs are deregulated in most cancers, including neuroblastoma. In this study, we analysed 430 miRNAs in 69 neuroblastomas by stem-loop RT-qPCR. Prediction of event-free survival (EFS) with support vector machines (SVM) and actual survival times with Cox regression-based models (CASPAR) were highly accurate and were independently validated...